Human hand bite causing soft tissue infection and finger amputation: A case report [İnsan isiriǧi sonrasi elde gelişen yumuşak doku enfeksiyonu ve parmak amputasyonu: Olgu sunumu] - (:unkn) unknown (My University, 2009)
A 50-year-old female patient presented to our institution with a human bite wound on her left hand. Her complaints started 15 days ago after her husband bit her hand. Oral antibiotics and local wound treatment had been given by another medical center to which she first presented. The treatment was changed to intramuscular antibiotics after her complaints worsened. T h e patient was neither hospitalized nor immobilized. She then presented to our clinic with deep wound infection. After hospitalization, intravenous (IV) antibiotics were given and open debridement was performed. F β hemolytic streptococci were isolated in cultures and I V antibiotic therapy was revised. T h e wound care and circulation of the second digit worsened despite the new therapy. As a result, ray-amputation through the second proximal metacarpal was performed. After amputation, the wound responded well to antibiotics and infection was resolved at the wound site. After one-year follow-up, she had minimal functional disability and all hand joints had full range of motion. In conclusion, hospitalization, I V antibiotic therapy and effective debridement should be performed in elderly patients who are at risk to achieve a favorable outcome.
Keywords: Debridement; Deep infection; Human bite